The Pioneer Organization and the School in Bulgaria: an Attempt to Discipline the Individual - Yancheva, Yana (Bulletin of the Institute of Ethnography SASA, 2022)
The article presents and analyzes the approaches, used by the Dimitrov’s pioneer organization (DPO) ‘Septemvrijče’ in Bulgaria to obsess and control the students and teachers’ school life (and in some aspects even their personal life), in order to prepare and discipline the future loyal citizens of the socialist society. The emphasis here is on Foucault’s concept of the ‘exam’ (in the broadest sense of the term) as a form of disciplinary control that should make the individuals visible and readable for the Authority. At the same time, I refer to Dejan Dejanov’s critical thesis about the double public gaze which allows the Authority to control both the examinees and the examiners. My research is based on a study of official documents of DPO ‘Septemvrijče’, school documents, biographical interviews and my own memories.
Keywords: childhood; school; pioneer organization; socialism; Foucault’s concept of the ‘exam